Mitigating chromium toxicity in oat (Avena sativa L.) with exogenous salicylic acid - Hassan, Hafiz Muhammad Mohsin; Abbas, Warda; Zehra, Syeda Sadaf; Zafar, Muhammad Uzair; Shehzadi, Anam (International Journal of Applied and Experimental Biology, 2026)
This study investigated the protective role of exogenous salicylic acid (SA) in mitigating chromium (Cr) toxicity in oat (Avena sativa L.). A pot experiment was conducted in a shade house using a factorial design with six treatment groups: Control (No Cr, No SA), CrCl3 2 mM, SA 0.5 mM, SA 2 mM, CrCl3 2 mM + SA 0.5 mM, CrCl3 2 mM + SA 2.0 mM. Chromium stress significantly reduced plant growth, yield, and anatomical parameters. Chromium treatment significantly decreased the root-shoot ratio, while both concentrations of SA improved growth considerably. The SA (2.0 mM) treatment proved to be most effective in enhancing overall plant growth and grain yield of oat. Anatomical analysis revealed that SA application mitigated the damage induced by Cr. Specifically, the thickness and area of stem sclerenchyma were significantly increased by 1.3- and 1.5-fold, respectively, with the 2.0 mM SA treatment compared to those in the control. Furthermore, SA improved the thickness of the leaf midrib, metaxylem, and phloem, as well as the root epidermis, endodermis, and phloem, particularly in the Cr + SA treatment. These anatomical changes are crucial for water conservation and overall plant survival under heavy metal stress. Our findings suggest that exogenous application of SA can effectively alleviate Cr-induced stress, promoting the healthy development of oat seedlings.